L-PRF associado ao enxerto gengival livre no “creeping attachment”: Estudo clínico randomizado. - Alves, Breno Edson Sendão [UNESP] (2018)
The main objective of the present clinic study will be to evaluate through observation of the root covering, the “creeping attachment” (CA) on Miller class II gingival recession treated with free gingival graft combined with leucocyte and platelet rich -fib rin (PRF-L). 12 patients with bilateral Miller Class II gingival recession in lower premolars were recruited . Group FGG (n= 12): control group, the site will receive the root coverage with free gingival graft, and Group FGG/L-PRF (n= 12): will be performed an association between free gingival graft and L-PRF, the L- PRF membrane stabilized to the receptor region and suturing the EGL. To obtain this platelet concentrate, 20 ml of blood of each patient will be collected and immediately centrifuged at 2700rpm for 12 minutes. The following parameters illbe measured: O`Leary plaque index, gingival index, eight of gingival recession, recession width, amount of eratinized mucosa, probing depth (PD) and then, the linical attachment level will be conducted. The measurements will be performed at 30, 90, 180 e 60 days after the surgical procedure . The CA will be measured at 90, 180 and 360 days. Data will be analyzed statistically (p < 0.05) in a specialized omputer program (Bioestat 5.0). After 360 days, ignifica nt differences were not found between the wo roups for CA, however there was a significant difference for keratinized gingiva, gingival height and linical attachment level. EGL and EGL/L -PRF are qually successful in the cree ping attachment gain in gingival recession of Miller class II.